Biocomposting technology and microbial populations of agroindustrial waste using pleurotus sajor-caju and earthworm (eudrilus eugeniae) - G. SAKTHIVIGNESWARI; G. SAKTHIVIGNESWARI; A. VIJAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2017)
Agro-waste can be considered as an important source for biocomposting technology as it contains more nutrients compared to other organic wastes. Biocompost has significant quantities of macro and micro-nutrients and beneficial microorganism. Corncob and coir pith are major agro-industrial wastes in India which decompose very slowly due to the presence of high amount of lignin, cellulose and hemi-cellulose components. The present study was aimed to analyze changes in the microbial population during the composting of corncob and coir pith. Six kinds of composting experiments were carried out by using corncob and coir pith. Microbial population was studied at regular intervals of 0-30, 30-60 and 60-90 days in the composting unit C1, C2, C3, C4, C5 and C6 during the composting period. The present study concluded that combined application of coir pith, Pleurotus sajor-caju and Eudrilus eugeniae - treated compost (C6) is microbiologically more active than other worm un-treated substrates.